1996
DOI: 10.3109/07357909609018904
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Carcinogenesis and Clinical Features of Asbestos-Associated Cancers

Abstract: Exposure to asbestos, particularly members of the amphibole subgroup (crocidolite, amosite), is associated with the development of malignant mesothelioma and lung cancer. Although management of asbestos in buildings and increased regulation of asbestos in workplace settings are viable approaches to the prevention of disease, the prognosis of asbestos-associated tumors is generally dismal. Moreover, although a vast amount of information is available on the responses of cells and tissues to fibers, understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
89
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 74 publications
0
89
1
Order By: Relevance
“…Its pathogenesis has been postulated to be associated with the generation of free radicals (Kamp et al, 1992;Mossman et al, 1996). In contrast to previous observations, which have shown that MnSOD is usually low in malignant tumours (Oberley and Buettner, 1979;Oberley and Oberley, 1997), we have recently shown that the mRNA level, immunoreactive protein and specific activity of MnSOD are highly expressed in the tumour cells of malignant mesotheliomas when compared to healthy pleura or non-malignant transformed human mesothelial cells (Met5A) (Kinnula et al, 1996;Kahlos et al, 1998).…”
contrasting
confidence: 49%
“…Its pathogenesis has been postulated to be associated with the generation of free radicals (Kamp et al, 1992;Mossman et al, 1996). In contrast to previous observations, which have shown that MnSOD is usually low in malignant tumours (Oberley and Buettner, 1979;Oberley and Oberley, 1997), we have recently shown that the mRNA level, immunoreactive protein and specific activity of MnSOD are highly expressed in the tumour cells of malignant mesotheliomas when compared to healthy pleura or non-malignant transformed human mesothelial cells (Met5A) (Kinnula et al, 1996;Kahlos et al, 1998).…”
contrasting
confidence: 49%
“…It is well known that malignant mesothelioma is caused by inhalation of asbestos [12,13]. In previous reports, it was shown that levels of oxidized pyrimidines and alkylated bases are strongly correlated with the length of occupational exposure to asbestos, and that an increase in the mutation frequency of lung DNA was induced by instillation with asbestos via the trachea [14,15].…”
Section: Malignant Mesothelioma and Antitumor Immunitymentioning
confidence: 99%
“…The pathogenesis of this disease is associated with exposure to asbestos fibres (Mossman et al, 1996). Recently, Simian virus-40 (SV-40) has been associated with this malignancy (Carbone et al, 1994).…”
mentioning
confidence: 99%